Analisis Kegiatan Pemuatan Peti Kemas Dari Depo Ke Kapal (Studi Kasus Pt. Sarana Bandar Nasional Cabang Tanjung Priok) - Afrisianto, Afrisianto; Bugis, Rafitra; Qamaruddin, Qamaruddin (Jurnal Ilmiah Wahana Pendidikan, 2024)
The purpose of this study is to determine the activity of loading containers from the depot to the ship and the obstacles that occur when carrying out these activities, and efforts to overcome them. The approach used in this research is descriptive qualitative. Data collection was carried out through observation, interviews and document studies. The results showed that the activity of loading containers from the depot to the ship at PT. Sarana Bandar Nasional Tanjung Priok branch includes stuffing, stripping, container delivery, container acceptance, Shipper Owner Container (SOC) receipt, ship loading process, depot relocation to container yard, container repair, heavy equipment division. In the activity of loading containers from the depot to the ship there are obstacles such as equipment damage, bad weather, truck delays, and lack of truck facilities. Efforts have been made to overcome these obstacles by carrying out among others: maintenance of equipment, training of workers, and provision of additional truck facilities.